2020
DOI: 10.1007/s10643-020-01054-4
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of the Literature on Aspects Affecting Positive Classroom Climate in Multicultural Early Childhood Education

Abstract: The risk for many young children from minority backgrounds of being excluded from a quality education might be reduced through the creation of a positive classroom climate. A systematic review was conducted to gain a better understanding of the pedagogical and structural aspects that foster a positive classroom climate in multicultural early childhood education settings. Following a systematic review procedure, 14 articles were selected and included in the analysis. The findings indicate that eight aspects con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(42 citation statements)
references
References 56 publications
0
36
0
6
Order By: Relevance
“…As research on school environment and climate shows, learning in a safe and supportive environment free of violence is essential for children's academic success, self-esteem, and wellbeing [2][3][4][5]. Developing positive feelings, such as friendship and empathy, is essential for ensuring such spaces in schools and classrooms [8,13,18,19]. In this case study we have looked at a School as a Learning Community, an interactive and whole-school educational model, in order to show whether and how the SEAs implemented there promote friendship and empathy, and their impact in improving the environment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As research on school environment and climate shows, learning in a safe and supportive environment free of violence is essential for children's academic success, self-esteem, and wellbeing [2][3][4][5]. Developing positive feelings, such as friendship and empathy, is essential for ensuring such spaces in schools and classrooms [8,13,18,19]. In this case study we have looked at a School as a Learning Community, an interactive and whole-school educational model, in order to show whether and how the SEAs implemented there promote friendship and empathy, and their impact in improving the environment.…”
Section: Discussionmentioning
confidence: 99%
“…It has been found that the quality of relationships and interactions within and outside the school among students, parents, and teachers is one of the main pillars in school environments promoting a positive climate [6,7]. Literature on school and classroom climates has shown that relationships based on feelings such as friendship are key in fostering safe and supportive environments, as it contributes to reducing conflicts [8]; to positive school experiences; and to a sense of school belonging [9], which is associated with emotional wellbeing [10]. It has also been found that friendship quality is associated with prosocial behavior towards friends [11], prosocial behavior being essential in promoting a positive school climate, and with better adjustment for early adolescents [12].…”
Section: Fostering Supportive and Safe Educational Environmentsmentioning
confidence: 99%
“…Findings point to a range of factors that can influence transphobic violence, as well as its intensity and consequences due to sociocultural factors [37,[51][52][53][54][55][56][57][58][59]. This subsection is divided into two given the pertinence of these factors: internal factors, such as felt gender identity, sexuality, and self-perception, and external factors, such as circumstances and judgments.…”
Section: Risk Factorsmentioning
confidence: 99%
“…In that sense, some indicators have been identified in the literature for the successful prevention and intervention of cases of distress and other forms of suffering by TNBAY. Several articles referred to the relevant role of family members, peers, school staff, and friends of the victims [52,53,56]. Their role was largely determined to be significant in the sections above, as they might be the perpetrators or passive witnesses in cases of violence against TNBAY.…”
Section: Possibilities To Prevent and Intervene In Cases Of Transphobmentioning
confidence: 99%
See 1 more Smart Citation